Título Padrão: muito além do verbal - Soares, Jessica Camila; Ribeiro, Ana Elisa (Informação em Pauta, 2021)
Among the most traditional professions of culture and information is that of the proofreader, although it is also one of the less regulated. It is included in the Brazilian offices classification (CBO) among the activities related to Communication, but there is little practical clarity about who this professional is and what his duties are. Previously seen as an advocate of grammatical rules, who sought only adjustments to the standard norm of language, today the proofreader, in addition to analyzing aspects such as cohesion, coherence, spelling and syntax, must also observe issues related to speech and to the context of production, circulation and reception of texts. In advertising and institutional texts, this kind of analysis aims to verify the grammar, but, far beyond that, also the wider context of language. Thus, the proofreader is faced with texts with various levels of reading and needs related to the demands of authors-clients, such as communicating, persuading and generating identification with the public. In addition, the proofreader of advertising and institutional texts needs to pay close attention to the multimodal aspects of the pieces he works with. Therefore, our aim here is to reflect about the needs of the training and the professional practices of proofreaders who work in organizational contexts, based on real graphic pieces.